1988
DOI: 10.1161/01.atv.8.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate exercise on serum lipids in young men with low high density lipoprotein cholesterol.

Abstract: Fifty-five healthy, sedentary, nonsmoking, and nonobese 24-to 26-year-old men who had low plasma concentrations of high density lipoprotein (HDL) cholesterol were selected for a study of the effect of short-term exercise on plasma llpld and lipoprotein concentrations. The participants were randomized Into two groups. Of these, 28 were assigned to a 9-week program of submaxlmal aerobic exercise three times weekly, and 27 were assigned to a nonexerclslng control group. Changes In physical fitness were assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
3

Year Published

1990
1990
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 26 publications
1
38
0
3
Order By: Relevance
“…Studies included-Of the 3750 citations reviewed, 21 met our inclusion criteria [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]39,40]. However, we were unable to include two studies because of the inability to retrieve necessary data for HDL 2 -C [39,40].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies included-Of the 3750 citations reviewed, 21 met our inclusion criteria [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]39,40]. However, we were unable to include two studies because of the inability to retrieve necessary data for HDL 2 -C [39,40].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, we were unable to include two studies because of the inability to retrieve necessary data for HDL 2 -C [39,40]. Thus, our percent loss that met our inclusion criteria was approximately 9%, leaving us with a total of 19 studies for analysis [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. A general description of the included studies is shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations